of, the, on Implementation of the International Convention Rules Concerning International Civil Aviation on Aircraft Hijacking (Ethiopian Airlines Boeing Case Study 767-300) - Appludnopsanji Appludnopsanji; Joko Setiyono (Fakultas Hukum Universitas Hang Tuah, 2020)
The hijacking of aircraft is a test in international criminal law. Besides of the fact that international conventions also control state authority, this issue is already present in international conventions, but also allows the State full power to enforce its national laws so that it can impose severe penalties on aircraft hijackers. The questions that form the basis of this legal inquiry are: how is the International Aircraft Hijacking Regulation and how to solve cases of Boeing 767-300 aircraft hijacking by Ethiopian Airlines. The empirical approach used in the drafting of this law is the standard legal approach. The analysis parameters used for this study are descriptive-analytical. The details for this analysis are International Convention Materials and Resources for the Library. The findings of the analysis concluded that the 1963 Tokyo Convention, the Hague Convention, the Montreal Convention, and the 1970 Hague Convention were concerned with the hijacking of aircraft. In the end, the suspects were prosecuted based on Ethiopian state authority as an aircraft registrar.